Re-interpreting the Environmentally Sound Management under Basel Convention - Fajar Ajie Setiawan (Padjadjaran Journal of International Law, 2022)
One of the fundamental principles of Basel Convention is the environmentally sound management (ESM), serving as a ‘meta-rule’, which establish the context within which bargaining under the Basel Convention takes place to develop more specific norms, such as rules regarding PIC, partnerships or management and technical guidelines of specific waste streams, regarding the management and transboundary movement of hazardous wastes. Yet, Basel Convention defines the crucial notion of ESM only in general terms, and has been subject to widely different interpretations and extensively criticized. Employing teleological approach which relies on the purpose of the Convention, this study argues that Basel Convention intended to establish a global convention with three principal aims: 1) minimization of hazardous wastes; 2) environmentally sound management of hazardous wastes; and 3) minimizing the transboundary movement of hazardous wastes. The central element of these aims was to limit such movements, as opposed to current practices of establishing ESM as the “least standard” for which transboundary movement of hazardous wastes would be allowed. Reinterpretation of ESM is also needed in light of the recent entry into force of Ban Amendment, which introduced ‘high risk’ as an element of consideration when addressing transboundary movements from developed countries to developing countries, which entails the applicability of precautionary principle in ESM interpretation.